2012
DOI: 10.1371/journal.pone.0033627
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modification of TLRs in Leukocytes Is Associated with Increased Susceptibility to Salmonella enteritidis in Chickens

Abstract: Toll-like receptors (TLRs) signaling pathways are the first lines in defense against Salmonella enteritidis ( S. enteritidis ) infection but the molecular mechanism underlying susceptibility to S. enteritidis infection in chicken remains unclear. SPF chickens injected with S. enteritidis were partitioned into two groups, one consisted of those from Salmonella-susceptible chickens (died within 5 d after injection, n = 6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 45 publications
(54 reference statements)
1
44
0
1
Order By: Relevance
“…Consistent with the present findings, DNA methylation of the TLR2-1 gene is higher in susceptible chickens infected with Salmonella enteritidis. 23 Moreover, malaria-induced epigenetic fine-tuning of TLR6 and TLR1 through DNA methylation of their gene promoters is important for the initial recognition and final outcome of P. chabaudi infection. 14 A trend towards DNA hyper-methylation of CpG sites of the TLR2 promoter is demonstrated in chronic periodontitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the present findings, DNA methylation of the TLR2-1 gene is higher in susceptible chickens infected with Salmonella enteritidis. 23 Moreover, malaria-induced epigenetic fine-tuning of TLR6 and TLR1 through DNA methylation of their gene promoters is important for the initial recognition and final outcome of P. chabaudi infection. 14 A trend towards DNA hyper-methylation of CpG sites of the TLR2 promoter is demonstrated in chronic periodontitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…1b). These two TLRs play important roles in the defense against Salmonella infection because susceptibility to Salmonella enteritidis is closely related to the responsiveness of three TLRs, namely, TLR4, TLR21, and TLR2 type 1 (Gou et al 2012). It is likely that the upregulation of IL1B and IL6 expression by LPS is caused by an interaction of LPS…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptor 4 (TLR4), an immunity-related gene, was found both differentially methylated and expressed between the Fayoumi and Leghorn lines [78]. A previous study has revealed that a susceptible chicken line had a greater methylation level of the TLR4 gene after infection [81] underlining the important role of this gene in the immune response. Thus, this study also highlighted the potential regulatory role of DNA methylation in the control of gene expression.…”
Section: The Chicken Dna Methylation Landscapementioning
confidence: 99%